The medical instructional questionnaire used to assess the quality of South African medical education - M.I.W. van Huyssteen; J.J. Blitz-Lindeque (South African Family Practice)
Background: Clinical training for medical students in the USA moved away from teaching hospitals to outpatient settings in diverse communities. It was thought that this use of ambulatory settings might adversely affect the quality of training of medical students and complicate control of the opportunities to which the individual student would be exposed. Concerns about the quality of medical training led to the development of a questionnaire to measure students' perceptions of their instruction. James and Shipengrover of the State University of New York at Buffalo developed and tested this student-completed questionnaire, the Medical Instructional Questionnaire (Med Ed IQ), which was based on quality improvement theory and grounded in experiential learning theory. Four constructs that contribute to instruction are measured by the questionnaire: preceptor activities that facilitate learning, learning opportunities, the learning environment and learner involvement. These constructs are measured as processes and are not intended to assess student performance. Many programme directors have an idea of which clinical sites and teachers provide better training, but a validated assessment of the process of instruction is necessary. To this end, the Med Ed IQ questionnaire has been tried and tested, and it has been suggested that, being a valid and reliable tool, it might assist in programme evaluation and provide benchmarks of quality over time to improve instruction in community-based practices. The clinical demands on clinician- teachers are heavy, and it is very important to help them achieve their educational objectives without diminishing their productivity. Devoting attention to conditions that improve the processes of teaching and learning, and measures that help monitor the quality of instruction in these settings, can therefore be beneficial.3 Among the implications of the use of the instrument is the provision of more specific feedback to preceptors on how to improve their quality of instruction. At the University of Pretoria in South Africa, several clinics are used in the experience-based training of senior medical students. The quality of the education that these students receive may vary between the different clinics because of different trainers who handle the circumstances and the students differently, different settings with different opportunities, and different patients who present different kinds of problems. We chose the Med Ed IQ questionnaire to elicit senior medical students' perceptions of the quality of training they received, their view of the preceptor and the benefits gained from active participation, and then compared the responses of the students who worked at the different clinics in order to identify problems and make recommendations to the clinician-teachers and the management of the different clinics.